Vertebral Augmentation of Cancer-Related Spinal Compression Fractures: A Systematic Review and Meta-Analysis. Issue 24 (15th December 2021) - Mattie, Ryan; Brar, Nick; Tram, Jennifer T.; McCormick, Zachary L.; Beall, Douglas P.; Fox, Andrew; Saltychev, Mikhail
Abstract : Comparison of pain relief with vertebral augmentation for the treatment of cancer-related vertebral compression fractures through meta-analysis of randomized controlled trials. Vertebral augmentation provides an overall positive clinically and statistically significant improvement in pain relief for spinal compression fractures due to metastatic disease. Abstract : Study Design: Systematic review and meta-analysis. Objective: To compare the magnitude and duration of pain relief with vertebral augmentation to any other therapy for the treatment of cancer-related vertebral compression fractures through meta-analysis of randomized controlled trials. Summary of Background Data: Derived from search on PubMed, EMBASE, CINAHL, Scopus, Central, Scopus, and Web of Science databases in May 2020. Studies selected were limited to randomized controlled trials comparing vertebral augmentation, either Balloon Kyphoplasty or Percutaneous Vertebroplasty (PVP) with or without additional therapy to any other intervention or placebo/sham. Methods: The methodological quality of each included study was assessed according to the Cochrane Collaboration's domain-based framework. Random effects model, Q test, and I 2 statistics were implemented. Results: Of 180 records identified, 7 were considered relevant, and included 476 participants. The risk of bias was considered "Low" in all studies. In five of the studies, vertebral augmentation alone (either PVP or Balloon Kyphoplasty) comprised one group, while comparative treatments included nonsurgical management, Kiva implantation, PVP and radiofrequency therapy, PVP and chemotherapy, PVP and intrasomatic injection of steroid, and PVP with 125 I seeds. Two studies compared PVP with an additional therapy against the standard of care. With regard to changes in pain severity, the effect sizes varied from 0.0 (95% –1.7 to 1.7) to –5.1 (95% –5.3 to –4.9). Most studies demonstrated a positive and statistically significant effect associated with PVP. Four of the seven studies demonstrated a clinically significant effect as well. Other than cement leakage, with an event rate of 0.24 (95% CI 0.11–0.44) or 24% (95% CI 11%–44%), there were no major adverse events consistently observed across multiple studies. Conclusions: The included randomized controlled trials demonstrated an overall positive and statistically significant effect of vertebral augmentation surgeries, such as vertebroplasty and kyphoplasty, for the treatment of cancer-related vertebral compression fractures, especially when compared with nonsurgical management, radiofrequency ablation, or chemotherapy alone. Level of Evidence: 1